Diversified dietary intake and associated factors among pregnant mothers attending antenatal care follow-up in public health facilities of Dire Dawa, Eastern Ethiopia. - Efrata Nigussie; Abebe Ferede; Melese Markos (Public Library of Science (PLoS), 2022)
Poor diversity dietary intake has great significance to women, pregnancy outcome and on her fetus or the growing and development of their baby collectively. Uncertainty of studies to examine whether pregnant women have been utilizing diversity dietary in their frequent intake and this has changed nutritional status. Therefore, this study aims to assess diversified dietary intake and associated factors among pregnant mothers attending antenatal care follow-up in public health facilities of Dire Dawa, Eastern Ethiopia. A facility-based cross-sectional study was conducted among 453 pregnant mothers randomly selected from the antenatal care unit at public health facilities from November 1-30/2020. Study subjects were selected with a systematic random sampling method from randomly selected antenatal care unity of health facilities in Dire Dawa Administration. A structured questionnaire and anthropometric measurements were used to collect data. Data were entered with kobo software and exported to Statistical Package for Social Science statistical software version 20 for analysis. Binary and multiple logistic regression models were used to declare the significance of independent variables at P<0.05. This study shows 55% (95% CI = (50-59.5) were inadequate diversified dietary intake. Having lower monthly income (Adjusted Odds Raito [AOR] = 4.4, Confident interval [95%CI] = 1.3-14.6), elementary educational status of mothers (AOR = 3.8, 95%CI = 1.5-9.9), consumption of two meals per day (AOR = 16.6, 95% CI = 2.04-135.8), didn't get antenatal care counseling (AOR = 2.2, 95% CI = 1.1-2.8) were significantly associated with diversified dietary. The result revealed that around 55% of respondents had inadequate dietary diversity. low household income, had less maternal education level and, consuming two meals per day, and no information about dietary diversity has contributed to inadequate dietary diversity. Accordingly, go forward in the right side of those variables were the core recommendation of this study.